Մեկ էջ 17-րդ դ. իրանահայ կերպարվեստի պատմությունից. նկարիչ Մինաս - Ստեփանյան, Աշոտ («Զանգակ - 97»)
In the XVII-XVIII centuries a considerable period of the Armenian history was closely related to Nor Jugha - the greatest Armenian colony of the Middle East, established in 1604/1605 in Iran. Surrounded by an alien cultural background here the Armenian culture, particularly the fine arts, reeeived their further development. One of the main chaiacteristics of Nor Jugha was the rise of popular painting with Minas as its most prominent representative.
Keywords: Նկարչություն; Արվեստ